2016
DOI: 10.1016/j.catena.2016.07.037
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biochar amendment on morphology, productivity and water relations of sunflower plants under non-irrigation conditions

Abstract: Three biochars (B1: pine wood, B2: paper-sludge, B3: sewage-sludge) produced under controlled pyrolysis conditions and one produced in kilns (B4: grapevine wood) were used as organic ameliorants in a Calcic Cambisol, which represents a typical agricultural soil of the Mediterranean region. This field study was performed with plants of sunflower (Helianthus annuus L.) at the experimental station "La Hampa", located in the Guadalquivir river valley (SW Spain). The soil was amended with doses equivalent to 1.5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
69
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(75 citation statements)
references
References 44 publications
6
69
0
Order By: Relevance
“…Considering the more specific characteristics for the field trial in the present study according to the classifications of Jeffery et al (2015) (biochar application rate of 51-60 t ha À1 ,~19% yield increase; wood biochar,~28% yield increase; initial pH of soil in the range of 7.1-7.5,~20% yield increase but not significant at the 5% level), a yield increase could have been expected. However, Paneque et al (2016) observed an increase in sunflower yield after application only with one of four biochars tested in a Mediterranean soil.…”
Section: Sunflower Yield In the Field Experimentsmentioning
confidence: 84%
See 1 more Smart Citation
“…Considering the more specific characteristics for the field trial in the present study according to the classifications of Jeffery et al (2015) (biochar application rate of 51-60 t ha À1 ,~19% yield increase; wood biochar,~28% yield increase; initial pH of soil in the range of 7.1-7.5,~20% yield increase but not significant at the 5% level), a yield increase could have been expected. However, Paneque et al (2016) observed an increase in sunflower yield after application only with one of four biochars tested in a Mediterranean soil.…”
Section: Sunflower Yield In the Field Experimentsmentioning
confidence: 84%
“…However, Paneque et al . () observed an increase in sunflower yield after application only with one of four biochars tested in a Mediterranean soil.…”
Section: Discussionmentioning
confidence: 94%
“…Table 8 also shows two trends. First, although various studies report increased water retention even at low rates of biochar application, two studies found that biochar only increased water retention when the amount applied was ³15 Mg ha -1 (Paneque et al, 2016;Xiao et al, 2016). This suggests that large amounts of biochar can be required to increase water retention consistently.…”
Section: Water Retention and Plant Available Watermentioning
confidence: 95%
“…The alterations in the water-holding capacity of soil have been widely studied (Paneque et al, 2016;Zhang et al, 2016). The application of biochar has shown a consistent increase in the water retention ability of soils, although the results are more noticeable in coarse-textured soils compared with fine-textured clay soils (Blanco-Canqui, 2017).…”
Section: How Might Biochar Improve Vegetablementioning
confidence: 99%